The Content of the Contract Between Freedom of Will and the Restrictions of the Legislator - Maadaoui, Nadjia (Journal of Legal Studies and Researches, 2017)
The intervention of the legislator is just in line with the contractual idea which is based on a balanced contract between the contractors, it does not mean that the deterioration or relapse contractual will, but achieving legal justice, and achieve a balance between all of the principle of authority will, pacta sunt servanda, and the trend towards restrictions imposed by the legislature, which indicates that the contract will no longer absolute but must be said objectively will. In accordance with the requirements of social need to give a great legislator and prominent role in overseeing the contract, the main objective of it, is to achieve justice and balance between the different interests of individuals.